Bogolyubov averaging and normalization procedures in nonlinear mechanics. I - Mitropolsky, Yu.A.; Lopatin, A.K. (Український математичний журнал, 1994)
A new method of asymptotic analysis of nonlinear dynamical systems is developed with extensive use of group-theoretical methods. The technique of normalization, which is named an "asymptotic decomposition" by the authors, is developed in the context of Bogolyubov averaging. In this paper, we also discuss how this technique helps to understand and develop the averaging method for systems in standard form and systems with several fast variables. The new method treats a centralized system as a direct analog of an averaged system according to Bogolyubov. The operation of averaging is interpreted as a Bogolyubov projector in the construction of the projection of an operator onto the algebra of the centralizer. Запропонований новий метод дослідженння нелінійних динамічних систем, розроблений на основі широкого застосуванння теоретико-групових методів. Розроблено техніку нормалізації у тісному зв'язку з методом усереднення М.М. Боголюбова, яка названа авторами асимптотичною декомпозицією. Розглянуто питання інтерпретації та розвитку методу усереднення щодо систем у стандартній формі та систем з кількома швидкими змінними. Новий метод інтерпретує централізовану систему як прямий аналог усередненої системи за Боголюбовим. Операція усереднення інтерпретується як проектор Боголюбова для побудови проекції будь-якого оператора на алгебру централізатора.